2010
DOI: 10.2527/jas.2009-2045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dam and sire genotypes on productive and carcass traits of rabbits1

Abstract: The aim of the experiment was to study the effect of dam and sire genotypes on the production and slaughter performance of growing rabbits. The experiment was carried out at Kaposvár University. Pannon White (PW) and maternal line (M) does were inseminated with the sperm of PW, M, large body line (LB), terminal line of Hycole hybrid (H), or colored line (CL) bucks. The mature body size of the M, PW, and CL genotypes was medium. The mature body size of the LB and H genotypes was large. Only PW and LB rabbits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
18
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
11
18
2
Order By: Relevance
“…The estimated correlation coefficient was moderate for the 1 st and 2 nd parities (-0.37 for both), but high for the 3 rd and 4 th parities (-0.53 and -0.70). Compared to other rabbit breeds, Szendrő et al (2010) observed that P rabbits have a lower amount of perirenal fat, which may suggest that the CT-aided selection decreased the rabbits' fat depots. This finding is unfavourable and can affect the P does, as it is known that energy deficit and depletion of body stores lead to a decrease in reproductive performance (Fortun-Lamothe, 2006).…”
Section: Genetic Correlationmentioning
confidence: 75%
See 1 more Smart Citation
“…The estimated correlation coefficient was moderate for the 1 st and 2 nd parities (-0.37 for both), but high for the 3 rd and 4 th parities (-0.53 and -0.70). Compared to other rabbit breeds, Szendrő et al (2010) observed that P rabbits have a lower amount of perirenal fat, which may suggest that the CT-aided selection decreased the rabbits' fat depots. This finding is unfavourable and can affect the P does, as it is known that energy deficit and depletion of body stores lead to a decrease in reproductive performance (Fortun-Lamothe, 2006).…”
Section: Genetic Correlationmentioning
confidence: 75%
“…Figure 2: The applied circular mating scheme (the arrows show the direction of the male transfer). (Nagy et al, 2010). 1, 2, 3, 4 are groups within each line.…”
Section: Population Foundation and Recorded Traitsmentioning
confidence: 99%
“…It has long been demonstrated that the rabbit's weight and age at slaughter markedly influence the meat quality (Ouhayoun and Dalle Zotte, 1993;Ouhayoun, 1998;Dalle Zotte, 2002;Szendrő et al, 2010). Meat quality differences due to gender depend on the slaughter age, as the differences between sexes become more evident as age gradually approaches puberty.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the favourable results, Szendr} o et al (2010) and Gyovai et al (2012) pointed out that TMV has a negative correlation with the LW21 (from À0.37 to À0.7). As a result, individuals with the best TMV may not have the best LW21 in the first step of selection.…”
Section: Introductionmentioning
confidence: 66%